1999
DOI: 10.1002/(sici)1097-4555(199907)30:7<557::aid-jrs418>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Raman scattering investigations in PrxY1−xAl3(BO3)4 single crystals

Abstract: The crystal growth, structure and Raman spectra of the Pr x Y 1−x Al 3 (BO 3 ) 4 (PYAB) single crystals are introduced. The experiments show that the characteristic lattice vibrational spectrum of the PYAB arises mainly from the internal vibrations of the BO 3 and AlO 6 groups, and that the rigidity of the lattice is mainly ascribed to the vibrations of B-O and Al-O bonds. For the Pr/YO 6 groups, there is no O 2− ion that is independent of the BO 3 and AlO 6 groups, and no new internal vibrational mode arises.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…As a matter of fact, previous studies on the vibrational spectra in YAB crystals have shown the presence of optical phonon modes at around 90 and 130 cm −1 , which have been associated with external vibration of the BO 3 and AlO 6 groups against the Yb/Y ions. Internal vibrations of those groups have also been identified by Raman spectroscopy at 420, 520, 620 and 700 cm −1 [31]. These lattice vibrations are also clearly observed in figure 8 modulating our optical spectra.…”
Section: Vibrational Structuresupporting
confidence: 79%
“…As a matter of fact, previous studies on the vibrational spectra in YAB crystals have shown the presence of optical phonon modes at around 90 and 130 cm −1 , which have been associated with external vibration of the BO 3 and AlO 6 groups against the Yb/Y ions. Internal vibrations of those groups have also been identified by Raman spectroscopy at 420, 520, 620 and 700 cm −1 [31]. These lattice vibrations are also clearly observed in figure 8 modulating our optical spectra.…”
Section: Vibrational Structuresupporting
confidence: 79%
“…It was observed that the decay times increase with the temperature from 240 µs at 10 K to about 350 µs at room temperature (see figure 4). This behaviour is similar to that observed for Dy 3+ in other hosts [21,22] and has yet to be satisfactorily explained. Two kinds of mechanism can be reasonably considered.…”
Section: Fluorescence Dynamicssupporting
confidence: 72%
“…The radiative lifetime calculated by means of the JO method is not far from the value observed for the 0.3% doped sample, even if the agreement is not fully satisfactory. Anyway, this allows us to conclude that multiphonon relaxation processes are inactive, as expected from the relatively large energy gap between the emitting and the next lower level (about 6200 cm −1 ), that requires the participation of at least five phonons, the maximum phonon energy of the lattice being 1378 cm −1 [21]. In order to obtain more information on the excited state dynamics of the Dy 3+ ion, the decay curves of the 2.8% doped crystal were measured as a function of the temperature and decay times were extracted from the long time exponential tail of the curves.…”
Section: Fluorescence Dynamicsmentioning
confidence: 99%
“…The fast decay, with a τ 1 lifetime of about 100 µs, is ascribed to the presence of a strong energy-transfer mechanism, due to the high doping level as already observed [12]. Moreover, the multiphonon relaxation is negligible, as the maximum phonon energy [19] is less than one fifth of the energy gap between the 4 F 9/2 level and the next lower one, and so the slow lifetime, τ 2 = 400 ± 10 µs, can be considered representative of the radiative decay. It is also possible to distinguish the number of ions decaying according to the different lifetimes.…”
Section: Resultsmentioning
confidence: 67%